Exploring the role of mitochondria in the changes seen in overall skeletal muscle health associated with ageing and cancer - Hatt, Jacob (2021)
Purpose: Pathological and age-related declines in both physical fitness and muscle function are well established; however, the role mitochondrial function plays in these changes is less understood. With low skeletal muscle mass and function associated with poorer surgical outcomes, treatments and interventions that can limit the decrease in muscle mass and function seen in the elderly, known as sarcopenia, and in those with cancer, known as cancer cachexia, is vital.